Arthropathy and proteinuria: nail-patella syndrome revisited - Albishri, Jamal (GMS German Medical Science, 2014)
[english] Nail-patella syndrome (NPS) is a pleiotropic autosomal-dominant disorder due to mutations in the gene LMX1B. It has traditionally been characterized by a tetrad of dermatologic and musculoskeletal abnormalities. However, one of the most serious manifestations of NPS is kidney disease, which may be present in up to 40% of affected individuals. Although diagnosis can be made at birth, it is often missed, presumably due to the rarity of the condition. A 35-year-old female presented to our clinic with history of small joint pain of 6 months duration. In addition she complained of pedal edema off and on for the last 12 years. Prior to her current presentation she had been managed by a local doctor symptomatically. On evaluation, a nephrotic syndrome was obvious, but no secondary cause could be found. However, her physical examination was characteristic of NPS and keeping in view the autosomal dominant nature of the disorder all her three siblings were screened who too showed classical features of NPS. This rare syndrome as a cause of nephrotic range proteinuria is discussed in this report. The report underlines the importance of a good physical examination in a given clinical setting.